Improving Information Flows for Remanufacturing - Kader, Oskar; Nykvist, Ida (My University, 2021)
Value creation in today’s economy is heavily based on a linear model, thus products are discarded at their end of life. The linear approach is a strong contributor to climate change and this is no exception for the automotive industry, which is currently facing new challenges to be more sustainable. In contrast to this model, the Circular Economy represents a regenerative and restorative model, which differs in value creation and instead aims to decouple economic growth from finite resource consumption. This report will mainly address how remanufacturing can be emphasized to increase circularity. This is easier said than done. The study aims to provide knowledge for industrial processes that support Volvo Cars in designing electric passenger car components for remanufacturing. This will further provide an action plan for the R&D unit, where in the process of remanufacturing Volvo Cars can improve to work towards a more circular mindset. More specifically, two questions will be answered: 1) What are the potential enablers and barriers to remanufacturing the electric transmission component in a circular economy context? And what aspects to take into consideration with components when designing for remanufacturing? and 2) What are the challenges Volvo Cars faces with the current remanufacturing strategy for vehicles? The findings of the study are as follows: First, internal and external enablers and barriers to remanufacture are identified and put into the context of Volvo Cars. Further, three main aspects to take into consideration when designing components for remanufacturing have been identified and been presented, which are technical, environmental, and economic aspects. Secondly, implications are presented based on each problem category for Volvo Cars and possible improvement areas identified. And third, the information between R&D and remanufacturing supplier was found to be the main barrier to overcome, thus a workshop was performed with the purpose of verifying this, as well as establish an action plan to overcome this and pave a trajectory to become circular.
Keywords: Circular Economy, Remanufacturing, Design for Remanufacturing, Information flow; Closed loop, Enablers, Barriers